Extra-short implants (≤ 6.5 mm in length) in atrophic and non-atrophic sites to support screw-retained full-arch restoration: a retrospective clinical study - Eduardo Anitua; Asier Eguia; Mohammad Hamdan Alkhraisat (SpringerOpen, 2023)
Abstract Purpose Increasing scientific evidence support extending the application of short dental implants to non-atrophic dental arches. The purpose of this study has been the evaluation of extra-short implants (≤ 6.5 mm in length) that were placed in atrophic and non-atrophic anatomical sites to support the same prosthesis. Methods For that, a retrospective study was conducted by including complete dentures that were solely supported by extra-short implants in the maxilla and/or the mandible. Clinical data about patients, implants, anatomy, and prosthesis were obtained. Statistical analysis was performed to assess implant- and prosthesis-survival, changes in the marginal bone level and prosthetic complications. Results A total of 87 implants in 15 screw-retained complete dentures were assessed. None of the prostheses nor the extra-short implant failed during the follow-up of 27.2 ± 15.4 months. The changes in the mesial and distal marginal bone level were + 0.15 ± 0.51 mm and + 0.11 ± 0.50 mm, respectively. Comparing the implants according to the availability of sufficient bone to place longer implants, indicated the absence of significant differences in the changes of the mesial marginal bone level. However, the changes in the distal marginal bone level showed a statistically significant difference in favor of implants that were placed in non-atrophic sites. Two events of screw loosening were reported that were resolved by retightening the screws. Conclusions Implant- and prosthesis-related outcomes support the use of extra-short implants in atrophic and non-atrophic site to support complete prosthesis. Graphical Abstract